Sengketa dalam Sektor Konstruksi di Indonesia - Robin Antonius Sanjaya (CV Rewang Rencang, 2025)
This study analyzes dispute resolution in the Indonesian construction sector, focusing on the preference for Arbitration and Alternative Dispute Resolution (ADR) mechanisms over traditional litigation. Indonesia's construction industry, intertwined with its political history and legal transformation, frequently faces disputes arising from payment delays, non-compliance with technical specifications, ambiguous contractual responsibilities, and land use conflicts. While litigation is available, Arbitration and ADR is favored due to its quicker, more cost-effective, and confidential processes. A normative legal research method is applied to examine legal phenomena through analytical evaluation of secondary data. Findings indicate that mediation and arbitration, in particular, are relevant for their flexibility, ability to preserve business relationships, and binding decisions. Arbitration stands out for its capacity to select expert arbitrators and apply the ex aequo et bono principle. The adoption of Arbitration and ADR aligns with Indonesian socio-cultural values like musyawarah-mufakat, which emphasize communal harmony and